2020
DOI: 10.3389/fpls.2020.00288
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile High Throughput Screening Platform for Plant Metabolic Engineering Highlights the Major Role of ABI3 in Lipid Metabolism Regulation

Abstract: Traditional functional genetic studies in crops are time consuming, complicated and cannot be readily scaled up. The reason is that mutant or transformed crops need to be generated to study the effect of gene modifications on specific traits of interest. However, many crop species have a complex genome and a long generation time. As a result, it usually takes several months to over a year to obtain desired mutants or transgenic plants, which represents a significant bottleneck in the development of new crop va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
3
8
0
Order By: Relevance
“…Collectively, these results reinforce the fact that WRI1 and ABI3, as the master regulators of oil accumulation, not only regulate gene expressions involved in fatty acid synthesis, but also control the expression of genes encoding for seed-specific oil-body storage proteins [ 53 , 63 , 72 , 73 ]. Therefore, WRI1-related regulation network of oil production in yellow nutsedge is most likely to differ either from oil seeds or oil fruits, possibly tuber-specific.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Collectively, these results reinforce the fact that WRI1 and ABI3, as the master regulators of oil accumulation, not only regulate gene expressions involved in fatty acid synthesis, but also control the expression of genes encoding for seed-specific oil-body storage proteins [ 53 , 63 , 72 , 73 ]. Therefore, WRI1-related regulation network of oil production in yellow nutsedge is most likely to differ either from oil seeds or oil fruits, possibly tuber-specific.…”
Section: Resultssupporting
confidence: 63%
“…In this respective, however, it is unclear whether ABI3 is the upstream regulator of WRI1 and controls WRI1 expression in the nutsedge tubers as in plant oilseeds. Recent study indicated that ABI3 played an important role in regulating plant oil accumulation, which might be independent from WRI1 and LEC2 regulation networks occurred in oil-rich seed tissues [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these results reinforce the fact that WRI1 and ABI3, as the master regulators of oil accumulation, do not only regulate gene expressions involved in fatty acid synthesis, but also control the expression of genes encoding for seed-speci c oil-body storage proteins [58,66,75,76]. Therefore, WRI1related regulation network of oil production in yellow nutsedge is most likely to differ either from oil seeds or oil fruits, possibly tuber-speci c.…”
Section: Great Transcriptional Divergence Of Tag Storage Genes Betweesupporting
confidence: 64%
“…In this respective, however, it is unclear whether ABI3 is the upstream regulator of WRI1 and controls WRI1 expression in the nutsedge tubers as in plant oilseeds. Recent study indicated that ABI3 played an important role in regulating plant oil accumulation, which might be independent from WRI1 and LEC2 regulation networks occurred in oil-rich seed tissues [66].…”
Section: Great Transcriptional Divergence Of Tag Storage Genes Betweementioning
confidence: 99%
“…Synthetic biology endeavours in plants are complicated by non‐negligible hurdles associated with genetic engineering, such as long timeframes for the generation of transgenic individuals, low rates of homologous recombination and, in some cases, cumbersome procedures for plant genetic transformation. However, populations of isolated cells, obtained from the enzymatic digestion of cell walls from plant tissues (typically young, poorly lignified leaves), can be adopted as an easy and convenient alternative to implement fast, combinatorial and high‐throughput tests for newly designed synthetic devices (Yoo, Cho and Sheen, 2007; Pouvreau et al , 2020). We therefore opted for this strategy to characterize the modules of split‐NlucOCP2.…”
Section: Discussionmentioning
confidence: 99%